2023
DOI: 10.3389/fimmu.2023.1111729
|View full text |Cite
|
Sign up to set email alerts
|

Induction of unique macrophage subset by simultaneous stimulation with LPS and IL-4

Abstract: Macrophages manifest as various subtypes that play diverse and important roles in immunosurveillance and the maintenance of immunological homeostasis in various tissues. Many in vitro studies divide macrophages into two broad groups: M1 macrophages induced by lipopolysaccharide (LPS), and M2 macrophages induced by interleukin 4 (IL-4). However, considering the complex and diverse microenvironment in vivo, the concept of M1 and M2 is not enough to explain diversity of macrophages. In this study, we analyzed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Our first observation analyzing the expression of M1 and M2 activation markers is that a mixed profile is present during T. crassiceps infection in the absence of IL-4 because increased expression of iNOS, Arginase, and RElm-α was observed simultaneously. Similar mixed expression was observed with macrophages stimulated with LPS/IL-4 [27]; also, it is widely recognized that helminth infections can induce a dual M1/M2 profile [28]. We also observed mixed IL-4/IFN-γ cytokine production in splenocytes from the Cre/LoxP mice.…”
Section: Discussionsupporting
confidence: 87%
“…Our first observation analyzing the expression of M1 and M2 activation markers is that a mixed profile is present during T. crassiceps infection in the absence of IL-4 because increased expression of iNOS, Arginase, and RElm-α was observed simultaneously. Similar mixed expression was observed with macrophages stimulated with LPS/IL-4 [27]; also, it is widely recognized that helminth infections can induce a dual M1/M2 profile [28]. We also observed mixed IL-4/IFN-γ cytokine production in splenocytes from the Cre/LoxP mice.…”
Section: Discussionsupporting
confidence: 87%
“…Based on the above results, we confirmed that PSCs serve as stem cells and found that MØs are likely involved in the biological regulation of PSCs after cranial injury. To explore the potential regulatory role of MØs, we examined both PSCs (PRRX1) and MØs in cranial periosteal tissue at various stages before and after injury (CD11B for macrophages and CD206 for the M2 subtype [ 32 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we investigated whether the negative impact of MGs/MΦs on iNSPCs was a result of a shift in MGs/MΦs toward the cytotoxic M1 type. To this end, MGs/MΦs were treated with IL4, which promotes a shift toward the M2 type [ 17 ]. FACS analysis showed that the rate of CD206 + MGs/MΦs increased from 57.3% to 79.4% following IL4 treatment ( Figure 3 I).…”
Section: Resultsmentioning
confidence: 99%